Membracidae of Gabon: the genus Hamma Buckton, 1905 (Hemiptera: Auchenorrhyncha) with description of three new species - Loudit, Sandrine Mariela Bayendi; Durante, Antonio; Susini, Antonio (Zootaxa, 2014)
Specimens of Membracidae belonging to the genus Hamma collected in several surveys conducted between 2009 and 2012 in Gabon were examined. They represent six species, of which three are described as new to science: Hamma boulardi n. sp., Hamma carlini n. sp., Hamma franciscae n. sp.